Dynamic frame length selection algorithm for slotted access in LTE-Advanced - Hongguang DUAN; Songpin LU; Lifei WANG; Sheng WANG; Tonghui LI; Dan TAN (Dianxin kexue)
Through analyzing the random access model of slotted access based channel access control protocol (SCACP) in LTE-Advanced system, an optimization algorithm for access frame length selection based on slotted access was proposed. The dynamic frame length selection in slotted access based on network real-time access load was realized. Moreover, the optimized access frame length was more suitable for current access load than before. It could ensure a high success rate of access, eliminate the unnecessary access delay and decrease the number of retransmissions to some extent. The simulation results demonstrate that the proposed dynamic frame length selection algorithm is more effective and practical.